Effect of Vasicine on Kidney Histomorphology in Streptozotocin-Induced Diabetic Wistar Rats - Sai Subhadra Ravali Kompella; Usha Kumary Santha; Thandavan Arthanari Kannan; Kalaiselvi Lakshmanan; Sridevi Ponnada (Majalah Biomorfologi, 2025)
Highlights1. Justicia adhatoda leaves can be used as herbal medicine to treat diabetes and its associated conditions. 2. Vasicine in Justicia leaves helps protect kidney health in individuals with diabetes.   Background: Justicia adhatoda is a perennial shrub with various potential quinazoline alkaloids viz., vasicine, vasicinone, deoxyvasicine, vasicol, adhatodinine and vasicinol. Objective: The present study aimed to study the effect of vasicine, a quinazoline alkaloid on diabetic nephropathy induced with Streptozotocin in rats. Material and Method: The vasicine was extracted from the leaves of Justicia adhatoda.  Thirty male Wistar rats were divided into four groups:  Negative control group (plain water orally), Positive control (single dose of streptozotocin 55mg/ kg b wt dissolved in citrate buffer pH 4.5 intraperitoneally), treatment groups III and IV respectively (Glibenclamide, 5mg/kg body weight dissolved in 0.5% DMSO; Vasicine @v0.9 mg/kg dissolved in 0.5% DMSO respectively). The blood glucose was monitored every week). Serum analysis for creatinine and Blood Urea Nitrogen was done. On day 28, the kidneys were removed and prepared for routine histopathological observation using H&E staining. The histopathological changes of the kidneys complied with the biochemical values. Result: Vasicine treatment helped restoring the renal histoarchitecture and reduced serum creatinine and blood urea nitrogen. Conclusion: Vasicine extracted from Justicia adhatoda can help in protecting diabetic nephropathy.